Graphene Oxide Hybridized nHAC/PLGA Scaffolds Facilitate the Proliferation of MC3T3-E1 Cells - Chunyong Liang; Yongchao Luo; Guodong Yang; Dan Xia; Lei Liu; Xiaomin Zhang; Hongshui Wang (Nanoscale Research Letters, 2018)
Abstract Biodegradable porous biomaterial scaffolds play a critical role in bone regeneration. In this study, the porous nano-hydroxyapatite/collagen/poly(lactic-co-glycolic acid)/graphene oxide (nHAC/PLGA/GO) composite scaffolds containing different amount of GO were fabricated by freeze-drying method. The results show that the synthesized scaffolds possess a three-dimensional porous structure. GO slightly improves the hydrophilicity of the scaffolds and reinforces their mechanical strength. Young’s modulus of the 1.5 wt% GO incorporated scaffold is greatly increased compared to the control sample. The in vitro experiments show that the nHAC/PLGA/GO (1.5 wt%) scaffolds significantly cell adhesion and proliferation of osteoblast cells (MC3T3-E1). This present study indicates that the nHAC/PLGA/GO scaffolds have excellent cytocompatibility and bone regeneration ability, thus it has high potential to be used as scaffolds in the field of bone tissue engineering.